HUBUNGAN GAYA KEPEMIMPINAN PARTISIPATIF DENGAN KINERJA KARYAWAN PADA PT TIRTATAMA ELPINDO - Angka Priatna; Hendra Muda Nasution (Universitas Pakuan, 2018)
The purpose of this study is to identify and analyze the performance of employees at PT TirtatamaElpindo. Relative to the how employees can work as good as possible and employees have highmotivation in completing the work with the appropriate participatory leadership style. Then about it, thisstudy aims to demonstrate the significance of the relationship participative leadership style with employeeperformance. The method that used is verification research, the research methods that used isexplanatory survey, engineering research using quantitative statistical and analytical methods that usedare spearmen rank correlation analysis, coefficient of determination and hypothesis test correlationcoefficient. Based on the results of the analysis, rank correlation coefficient spearmen participativeleadership style and employee performance is obtained r = 0.183. That is a very low that showed therelationship between the two variables. Value Coefficient of Determination = 3.35% so it can be said thata participatory leadership style has contributed 3,3,5% in affecting employee performance while factors -other factors have contributed 96.65% in affecting employee performance. And of the results ofhypothesis testing, the participative leadership style with employee performance at PT. Tirtatama Elpindothere was no a real relationship. Because t hitung (1,447) t table (2.048), then accept and reject Ho Ha.The conclusion that there is no real relationship between participatory leadership style with employeeperformance.